Budaya Nomad dalam Pertarungan Wacana Musik Industri Indonesia Studi Kasus: Boy-Girl Band - Nofer, Dolly; Pitana, Titis Srimuda; Susanto, Dwi (citeus, 2019)
Boy-girl band K-Pop music appearing in Indonesian music industry is a discourse contruction, teritorial or music life style which is brought by pop culture and Korean culture industry. The intrance of this music culture then cause a few problems which are the battle of discourse and the construction of the K-Pop music discourse itself, which does the culture migration for any purpose. For, this research is due to solve the problems, (1) boy-girl band as once of music life style discourse, (2) boy-girl band music discourse in battle arena of music life style, and (3) impact of K-Pop discourse construction through boy-girl band. The perspective which is used in discussing those problems are concepts of territori and discourse in Cultural Studies. The data used are aesthetic discourse—surrounds the K-Pop boy-girl band. The result of this research shows that K-pop boy-girl band is a battle arena of music life style in context popular culture, consumerism, and identity struggle of Korean culture. Then, it causes the impact to music discourse in Indonesian music industry, which internalizes K-pop values—locality is other subject in Indonesian music industry discourse.